Lead‐Free Highly Efficient Blue‐Emitting Cs3Cu2I5 with 0D Electronic Structure. Issue 43 (14th September 2018) - Jun, Taehwan; Sim, Kihyung; Iimura, Soshi; Sasase, Masato; Kamioka, Hayato; Kim, Junghwan; Hosono, Hideo
Abstract: Halide perovskites, including CsPbX3 (X = Cl, Br, I), have gained much attention in the field of optoelectronics. However, the toxicity of Pb and the low photoluminescence quantum yield (PLQY) of these perovskites hamper their use. In this work, new halide materials that meet the requirements of: (i) nontoxicity, (ii) high PLQY, and (iii) ease of fabrication of thin films via the solution process are explored. In particular, copper(I) halide compounds with low‐dimensional electronic structures are considered. Cs3 Cu2 I5 has a 0D photoactive site and exhibits blue emission (≈445 nm) with very high PLQYs of ≈90 and ≈60% for single crystals and thin films, respectively. The large exciton binding energy of ≈490 meV explains well the 0D electronic nature of Cs3 Cu2 I5 . Blue electroluminescence of Pb‐free halides is demonstrated using solution‐derived Cs3 Cu2 I5 thin films. Abstract : 0D Cs3 Cu2 I5 is used to synthesize a single crystal and thin film. This material is nontoxic, inexpensive, and air‐stable and exhibits high photoluminescence quantum yields of 90% (single crystal) and 60% (thin film). Further, Cs3 Cu2 I5 has a 0D photoactive site and a large exciton binding energy of ≈490 meV, which explains the 0D optoelectronic nature of Cs3 Cu2 I5 .